2017
DOI: 10.1155/2017/7906859
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Methane Concentration by Removing Contaminants from Biogas Mixtures Using Combined Method of Absorption and Adsorption

Abstract: We report a laboratory scale combined absorption and adsorption chemical process to remove contaminants from anaerobically produced biogas using cafeteria (food), vegetable, fruit, and cattle manure wastes. Iron oxide (Fe2O3), zero valent iron (Feo), and iron chloride (FeCl2) react with hydrogen sulfide (H2S) to deposit colloidal sulfur. Silica gel, sodium sulfate (Na2SO4), and calcium oxide (CaO) reduce the water vapour (H2O) and carbon dioxide (CO2). It is possible to upgrade methane (CH4) above 95% in bioga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…As discussed in previous reviews, effective mixing can lead to a homogeneous distribution of both nutrients and substrate, it also leads to a uniform distribution of the major bacterial and archaeal classes. A high abundance of methanogens at the top could be partially attributable to the better methane production observed in the BMP test in various studies [124][125][126][127][128][129].…”
Section: Gas Chromatography (Gc)mentioning
confidence: 96%
“…As discussed in previous reviews, effective mixing can lead to a homogeneous distribution of both nutrients and substrate, it also leads to a uniform distribution of the major bacterial and archaeal classes. A high abundance of methanogens at the top could be partially attributable to the better methane production observed in the BMP test in various studies [124][125][126][127][128][129].…”
Section: Gas Chromatography (Gc)mentioning
confidence: 96%
“…Several previous studies have reported that biogas produced from untreated rice straw is composed of methane (CH 4 , ~50-75%), carbon dioxide (CO 2 , ~25-50%), other impurities in small quantities such as water (H 2 O, ~5-10%), hydrogen sulfide (H 2 S, ~0.005-2%), siloxanes (0-0.02%), oxygen (O 2 , ~0-1%) and nitrogen (0-2%) [20][21][22][23]. Biogas is enriched by removing unwanted gases (CO 2 , H 2 S and water vapor) to increase the calorific value, so that it is economical to compress and transport to longer places for distribution or move to other area for multifaceted applications [24][25][26].…”
Section: Anaerobic Digestion Of Lignocellulosic Biomassmentioning
confidence: 99%
“…The processes involving CO 2 capture and storage are gaining attention as an alternative for reducing CO 2 concentration in the enrichment of biogas [22,28,29]. Several physiochemical [22,[30][31][32], biological [33,34] and thermal methods [29,35] for biogas enrichment process or purification of biogas have been reported [20,29] ( Table 1). For example, purification of biogas using calcium hydroxide (Ca(OH) 2 ) solution, thus CO 2 would be reacted with Ca(OH) 2 solution to form the precipitate of calcium carbonate (CaCO 3 ) has been reported [36].…”
Section: Biogas Enrichmentmentioning
confidence: 99%
“…Biogas produced from anaerobic digestion can be treated with techniques such as biofiltration, pressurized water scrubbing, refrigeration/chilling and combined adsorption and absorption process. The four methods have benefits and drawbacks [19]. Water scrubbing and biofiltration have excellent hydrogen sulphide, ammonia and volatile organic compound removal efficiency, while refrigeration is efficient for water vapour and ammonia removal [20].…”
Section: Introductionmentioning
confidence: 99%
“…Water scrubbing and biofiltration have excellent hydrogen sulphide, ammonia and volatile organic compound removal efficiency, while refrigeration is efficient for water vapour and ammonia removal [20]. Combined adsorption and absorption effectively remove water vapour, hydrogen sulphide, carbon dioxide and ammonia [19] and [20]. The aim of the study is to generate biogas from cassava peel using cow dung as inoculum and purifying the gas to get a higher methane concentration.…”
Section: Introductionmentioning
confidence: 99%